Raylan ebook A novel. - Leonard, Elmore (Raylan Givens, 2012)
"Elmore Leonard can write circles around almost anybody active in the crime novel today." —New York Times Book Review The revered New York Times bestselling author, recognized as "America's greatest crime writer" (Newsweek), brings back U.S. Marshal Raylan Givens, the mesmerizing hero of Pronto, Riding the Rap, and the hit FX series Justified. With the closing of the Harlan County, Kentucky, coal mines, marijuana has become the biggest cash crop in the state. A hundred pounds of it can gross $300,000, but that's chump change compared to the quarter million a human body can get you—especially when it's sold off piece by piece. So when Dickie and Coover Crowe, dope-dealing brothers known for sampling their own supply, decide to branch out into the body business, it's up to U.S. Marshal Raylan Givens to stop them. But Raylan isn't your average marshal; he's the laconic, Stetson-wearing, fast-drawing lawman who juggles dozens of cases at a time and always shoots to kill. But by the time Raylan finds out who's making the cuts, he's lying naked in a bathtub, with Layla, the cool transplant nurse, about to go for his kidneys. The bad guys are mostly gals this time around: Layla, the nurse who collects kidneys and sells them for ten grand a piece; Carol Conlan, a hard-charging coal-mine executive not above ordering a cohort to shoot point-blank a man who's standing in her way; and Jackie Nevada, a beautiful sometime college student who can outplay anyone at the poker table and who suddenly finds herself being tracked by a handsome U.S. marshal. Dark and droll, Raylan is pure Elmore Leonard—a page-turner filled with the sparkling dialogue and sly suspense that are the hallmarks of this modern master.